Peri and intraglomerular haematoxylinophilic deposits in a newborn: answer - Sonia Nemolato; Alice Sanna; Clara Gerosa; Daniela Fanni; Giuliana Palmas; Melania Puddu; Cristina Loddo; Claudia Fanni; Peter Van Eyken; Gavino Faa (Hygeia Press di Corridori Marinella, 2013)
Idiopathic infantile arterial calcification (IIAC) is a rare disease characterized by abnormal calcification of the arterial vessels, resulting in calcium deposits in the wall of medium-sized and large arteries. IIAC is caused by mutations in the ENPP1 gene, localized on chromosome 6q22, resulting in deficiency of the enzyme PC-1 nucleoside triphosphate pyrophosphohydrolase (NPP). Clinical presentation may occur during the intrauterine life, with fetal hydrop, aorto-pulmonary calcification, or as fatal hypertensive cardiomyopathy. In other patients, the clinical presentation is in the postnatal period with hypertrophic cardiomyopathy, with a fatal outcome within 6 months due to intractable heart failure. Here we report the clinico-pathological findings of a preterm affected with IIAC, with particular emphasis on renal glomerular pathological lesion not previously described in this disease.